Non-Lethal and Lethal Tools to Manage Wolf-Livestock Conflict in the Northwestern United States - Bangs, Ed; Jimenez, Mike; Niemeyer, Carter; Fontaine, Joe; Collinge, Mark; Krsichke, Rod; Handegard, Larry; Shivik, John A.; Sime, Carolyn; Nadeau, Steve; Mack, Curt; Smith, Douglas W.; et al. (Proceedings of the Vertebrate Pest Conference, 2006)
Gray wolf populations were eliminated from the northern Rocky Mountains of the western United States by 1930, largely because of conflicts with livestock. The wolf population is now biologically recovered and over 1,020 wolves are being managed in Montana, Idaho, and Wyoming under the federal Endangered Species Act. From 1987 to December 2005, 528 cattle, 1,318 sheep, 83 dogs, 12 goats, 9 llamas, and 6 horses were confirmed killed by wolves, and over $550,000 was paid from a private damage compensation fund. To help restore the wolf population, we used 22 variations of non-lethal control tools, relocated wolves 117 times, and killed 396 wolves to reduce conflict between wolves and livestock. A variety of tools, including regulations that empower the local public to protect their private property, reduced the probability of wolf-caused damage. This wolf population was restored, the risk of livestock damage reduced, and public tolerance of wolves improved through an integrated program of proactive and reactive non-lethal and lethal control tools. Reduced conflict increases the potential to restore wolf populations.